The Saving Matrix Method for Improving Distribution Efficiency - Rinjani Tri Wulandari; Anton Mulyono Azis (Jurnal Manajemen Indonesia, 2022)
The delivery route for the Bandung 40400 Mail Processing Center is determined based on the estimation using the zoning system, and this may trigger delays. This happens because of each vehicle can only deliver to one distribution center at a time. This makes the load factor level of vehicle utilization below 20%. This study aims to obtain the optimal route and delivery schedule to improve distribution efficiency and increase the load factor of vehicle capacity utilization. This quantitative research method uses the Saving Matrix algorithm on all distribution channels. The results obtained indicate that the optimal delivery routes are 5 to 6 cluster. This saves mileage of up to 144 km per route per day and saves distribution costs of up to Rp. 39,146.50 for one delivery. In addition, there was an increase in the load factor of 18.37% for dropping 1 and 16.49% for dropping 2. By using the proposed route, a resume of the delivery schedule is obtained with clearer departure and arrival times and saving times up to 275 minutes. Furthermore, the expansion of the scope of research and comparing the level of effectiveness between distribution centers in various regions can be carried out as a follow-up study. Keywords—Saving matrix algorithm; Delivery routes; Load factor; Scheduling